Wellspring - Giles, Janice Holt (Book collections on Project MUSE., 2002)
The last book Giles published before her death in 1979, Wellspring has been out of print for years. The nineteen selections bring together Giles's fiction, nonfiction, autobiography, and fictionalized autobiography to reveal a behind-the-scenes look at her life, her family, her love for her adopted state of Kentucky and its people, her politics, her favorite authors, her thoughts on writing, and her views of her own work. Wellspring is available again for old and new readers of Janice Holt Giles. Janice Holt Giles (1905-1979), author of nineteen books, lived and wrote near Knifley, Kentucky,